Digital Transaction Processes and Their Evaluation in Uzbekistan Banks (Texas Journal of Multidisciplinary Studies, 2024)
In this article, the importance of digital transaction processes in Uzbek banks is about ensuring security, speed, and reliability for banks and financial organizations when customers use these processes to exchange money transfers in their daily activities